Structural relationships of organizational identity and organizational citizenship behaviour among Malaysian hotel employees / Hashim Fadzil Ariffin, Raja Puteri Saadiah Raja Abdullah and Noradzhar Baba - Ariffin, Hashim Fadzil; Raja Abdullah, Raja Puteri Saadiah; Baba, Noradzhar (2015)
The main objective of this study is to investigate the structural rela-tionships between organizational identity (OI) and organizational citizenship behaviour (OCB) among Malaysian hotel employees. The aim is to identify the perception of employees concerning the OI and OCB that they have perceived at their workplace. The data have been collected through sets of questionnaire answered by 624 respondents who are hotel employees in Malaysia. The result of this study reveals that OI and OCB are perceived as valid constructs. Findings also show that there is a relationship between OI and OCB, and is confirmed through Structural Equation Modeling. Re-spondents perceive that the more they possess OI, the more they re-act in OCB manners. Limitations and future research directions are also discussed.